Nurturing Sustainable Consumption: Social Learning and Behavioral Change Fostered by Grassroots Food Initiatives in Galicia, Spain - Lema Blanco, Isabel; García Mira, Ricardo (Sustainability, 2026)
Considering sustainable consumption not just as an exercise of individual choice but a shared and collective activity, this study explores the role of conscious and responsible consumption initiatives (CRCIs) driving citizens’ adoption of sustainable lifestyles. This research followed a qualitative approach, combining documentary research and twenty-six in-depth interviews with practitioners in eight grassroots consumer initiatives located in Galicia (Spain). The results show that CRCIs favor members’ consumption of organic, seasonal, fair, and locally produced food. The findings also reveal that engagement in these initiatives nurtures three interconnected types of learning—cognitive, attitudinal, and behavioral—which contribute to wider adoption of sustainable practices related to shifts in dietary habits, energy use, mobility, and frugality. CRCIs facilitate gradual transitions toward reduced meat consumption, favoring the intake of plant-based foods, and greater self-efficacy in preparing sustainable meals. These behavioral changes are incremental, motivated by inner reflection, practical experience, and consciousness around alternative economic models. However, the consistent adoption of sustainable eating habits is hindered by cultural and psychological barriers like cultural traditions, entrenched habits, and time constraints. In conclusion, these grassroots initiatives are interesting entry points for engaging citizens in sustainable lifestyles, becoming also gateways to the broader social and solidarity economy movement.
Keywords: sustainable food consumption; low-carbon diets; vegetarian diets; social learning; behavioral spillover; food co-ops; grassroots social innovations; green lifestyles; consumer behavior; barriers and drivers